Analysis and strengthening of carpentry joints - Branco, Jorge M. (2015)
Joints play a major role in the structural behaviour of old timber frames [1]. Current standards mainly focus on modern dowel-type joints and usually provide little guidance (with the exception of German and Swiss NAs) to designers regarding traditional joints. With few exceptions, see e.g. [2], [3], [4], most of the research undertaken today is mainly focused on the reinforcement of dowel-type connections. When considering old carpentry joints, it is neither realistic nor useful to try to describe the behaviour of each and every type of joint. The discussion here is not an extra attempt to classify or compare joint configurations [5], [6], [7]. Despite the existence of some classification rules which define different types of carpentry joints, their applicability becomes difficult. This is due to the differences in the way joints are fashioned depending, on the geographical location and their age. In view of this, it is mandatory to check the relevance of the calculations as a first step. This first step, to, is mandatory. A limited number of carpentry joints, along with some calculation rules and possible strengthening techniques are presented here.